Impact of Green Innovation and Corporate Social Responsibility on Firm Reputation with Mediation of Environmental Performance (Journal of Social Sciences Review, 2024)
A company's long-term viability and prosperity depend on intangible assets like its reputation which is especially important in today's globally interconnected business environment. In light of natural resource based view theory (NRBV), the objective of this study is to explore the effect of corporate social responsibility (CSR) and green innovation (GI) on environmental performance (EP) and firm reputation (FR). Additionally, it looks into how EP affects FR. Moreover, it explores the function of EP as a mediator between the GI-FR and CSR-FR linkages, previously neglected.  Primary data were collected from managers of manufacturing industries via questionnaire and analyzed using SmartPLS 3.2.9. A total of 283 responses were collected using convenience sample technique. The findings of PLS-SEM revealed that GI, CSR and EP have significant impact on FR. Additionally, GI and CSR have substantial impact on EP. The connections between GI-FR and CSR-FR are partially mediated by EP. This research adds to the literature by examining mediating function of EP in the relationships between GI-FR and CSR-FR. The study also has implications, limitations and future directions.
Keywords: Green Innovation; Corporate Social Responsibility; Environmental Performance; Firm Reputation